2009
DOI: 10.3858/emm.2009.41.1.003
|View full text |Cite
|
Sign up to set email alerts
|

Thromboxane A2modulates migration, proliferation, and differentiation of adipose tissue-derived mesenchymal stem cells

Abstract: Prostanoid metabolites are key mediators in inflammatory responses, and accumulating evidence suggests that mesenchymal stem cells (MSCs) can be recruited to injured or inflamed tissues. In the present study, we investigated whether prostanoid metabolites can regulate migration, proliferation, and differentiation potentials of MSCs. We demonstrated herein that the stable thromboxane A 2 (TxA 2 ) mimetic U46619 strongly stimulated migration and proliferation of human adipose tissue-derived MSCs (hADSCs). Furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 28 publications
1
34
0
Order By: Relevance
“…However, others reported that TP blockers suppressed migration and angiogenesis of human umbilical vein ECs and human dermal microvascular ECs, 44 TxAS overexpression observed in nonsmall cell lung cancers promotes tumor growth and VEGF secretion, 45,46 and activation of TP induced the differentiation of human ASCs to smooth muscle-like cells. 47,48 The discrepancies are probably ascribed to different cells and different approaches used, and perhaps different downstream signaling is mediated by TP receptors.…”
Section: Discussionmentioning
confidence: 99%
“…However, others reported that TP blockers suppressed migration and angiogenesis of human umbilical vein ECs and human dermal microvascular ECs, 44 TxAS overexpression observed in nonsmall cell lung cancers promotes tumor growth and VEGF secretion, 45,46 and activation of TP induced the differentiation of human ASCs to smooth muscle-like cells. 47,48 The discrepancies are probably ascribed to different cells and different approaches used, and perhaps different downstream signaling is mediated by TP receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, activation of p42/44 MAPK, an essential intracellular trigger of migratory behavior of stem cells ( 45,46 ), has recently been shown to confer the promigratory effect of cannabidiol on MSCs ( 33 ). However, the impact of the endocannabinoids, AEA and 2-AG, or the endocannabinoid-like substances, OEA and PEA, on the migratory action of MSCs is largely unknown.…”
Section: Migration Assaymentioning
confidence: 99%
“…Thromboxane A 2 , a product of AA metabolism, appears to play a key role in the migration, proliferation, and differentiation of human adipose tissuederived mesenchymal stem cells into smooth muscle-like cells through signaling mechanisms involving ERK and p38 MAPK [89]. This action of TXA 2 on migration and proliferation of stem cells may have relevance to the metastatic properties shown by some tumor cells.…”
Section: Efas/pufas and Their Metabolites In Stem Cell Proliferation mentioning
confidence: 96%